2018
DOI: 10.1155/2018/6463807
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeraniol Prevents Statin‐Dependent Myotoxicity in C2C12 Muscle Cells through RAP1 GTPase Prenylation and Cytoprotective Autophagy

Abstract: The present study investigated the cytotoxic effects of statins (atorvastatin (ATR) and simvastatin (SIM), resp.) and methyl-beta-cyclodextrin (MβCD), at their respective IC50 concentrations, on muscle regeneration in the in vitro model of murine C2C12 myoblasts. Cotreatment with mevalonate (MEV), farnesol (FOH), geranylgeraniol (GGOH), or water-soluble cholesterol (Chol-PEG) was employed to determine whether the statin-dependent myotoxicity resulted from the lower cholesterol levels or the attenuated synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 66 publications
5
33
1
Order By: Relevance
“…This investigation has verified findings from in vitro studies 22,27,30,32 and demonstrated that supplementation with GGOH can prevent statin-induced skeletal muscle fatigue in rodents. Gastrocnemius muscles isolated from the SIM group exhibited a significant decline in muscle force production, an effect which is characteristic of this rodent model as well as statininduced myalgia in clinical practice.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This investigation has verified findings from in vitro studies 22,27,30,32 and demonstrated that supplementation with GGOH can prevent statin-induced skeletal muscle fatigue in rodents. Gastrocnemius muscles isolated from the SIM group exhibited a significant decline in muscle force production, an effect which is characteristic of this rodent model as well as statininduced myalgia in clinical practice.…”
Section: Discussionsupporting
confidence: 80%
“…GGPP was administered as its precursor, GGOH, owing to its greater cell/tissue permeability. 32 GGOH was dissolved in saline and delivered at a dose of 15 mg kg À1 day À1 . This concentration was used as it was calculated to be an equivalent mid-range dose (per kg bodyweight) to that which has previously been delivered to rats.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired prenylation of the Rap1 protein leads to lower muscle cell viability (repressed protein synthesis) and impeded autophagy. This mechanism might explain muscle damage and hampered myogenesis in statin-dependent myopathies [ 65 ].…”
Section: Rap1 In Skeletal Muscle Differentiationmentioning
confidence: 99%
“…Consequently, the regeneration and growth of skeletal muscle is inhibited. Our studies on C2C12 cells show that the Rap1, which becomes active due to prenylation with geranylgeraniol, plays a key role in the IGF-1/PI-3K/Akt1 signaling pathway [ 65 ].…”
Section: Rap1 In Skeletal Muscle Differentiationmentioning
confidence: 99%